2019
DOI: 10.33545/2616454x.2019.v3.i3a.94
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Indian rishi’s (Sages) knowledge of botany and medicinal plants since Vedic period was much older than the period of Theophrastus, A case study-who was the actual father of botany?

Abstract: In India, the study of Taxonomical rank classification and naming of plants in Sanskrit language is much older than that of Latin and Greek languages and the study dates back to Vedic period from 2500 BC to 600 BC. In Rigveda, three groups of plants have been recognised, viz. trees (Briksha), herbs (Osadhi) and creepers (Virudh). These are further classified into flowering, non-flowering, fruit bearing and fruitless plants. Atharva Veda also contains descriptions of many medicinal plants. In the ancient Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, new drugs should be introduced to combat such resistant strains without having adverse side effects. The Indian holy literature Rigveda and Atharvaveda, two of the four Vedas (Hindu holy scripture), outline the history of plants and its uses 19 . Additionally, ethanobotanist revealed that plants have hiostorically been used to fight malaria 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, new drugs should be introduced to combat such resistant strains without having adverse side effects. The Indian holy literature Rigveda and Atharvaveda, two of the four Vedas (Hindu holy scripture), outline the history of plants and its uses 19 . Additionally, ethanobotanist revealed that plants have hiostorically been used to fight malaria 20 .…”
Section: Introductionmentioning
confidence: 99%